2021
DOI: 10.1007/s10798-021-09677-3
|View full text |Cite
|
Sign up to set email alerts
|

Cultivating students’ computational thinking through student–robot interactions in robotics education

Abstract: This research focuses on student–robot interaction in the learning environment of robotics education (RE) and attempts to explore how it cultivates students’ computational thinking (CT). Different from child–robot interactions as investigated in the social robot field, student–robot (S–R) interactions focus mainly on the process of interaction between learners and programmable robot kits in RE settings. At a four-week robotics summer camp in China, mixed-methods research was conducted. Forty primary school stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 45 publications
1
15
0
3
Order By: Relevance
“…Gadzikowski [6] designed coding, robotics, and engineering course for young students to learn knowledge, such as coding, robotics and engineering concepts, and practice skills, such as creative problemsolving, computational thinking, and critical thinking. Qu and Fok [7] focused on student-robot interactions in robotic education and attempted to cultivate student's computational thinking skills. Chevalier et al [8] discussed how educational robotics fostered computational thinking skill development and confirmed that robotic education is necessary for specific teaching interventions.…”
Section: Computationalmentioning
confidence: 99%
See 1 more Smart Citation
“…Gadzikowski [6] designed coding, robotics, and engineering course for young students to learn knowledge, such as coding, robotics and engineering concepts, and practice skills, such as creative problemsolving, computational thinking, and critical thinking. Qu and Fok [7] focused on student-robot interactions in robotic education and attempted to cultivate student's computational thinking skills. Chevalier et al [8] discussed how educational robotics fostered computational thinking skill development and confirmed that robotic education is necessary for specific teaching interventions.…”
Section: Computationalmentioning
confidence: 99%
“…In this study, the top 30% of students were selected as the excellent category, i.e., category A, the bottom 20% as the average category, i.e., category C, and the rest as the medium category, i.e., category B. us, the initial category classification of the evaluated subjects was completed. e initial classification of the three categories of students, that is, the tripartition, is A � [10,7,24,23,20,5,6,22,18], B � [9,19,4,25,13,8,21,12,28,11,15,3,17,14,29], and C � [1, 26, 27, 16, 2, 0], respectively.…”
Section: An Illustrative Examplementioning
confidence: 99%
“…Educational researchers have been actively seeking innovative methods and ways to incorporate CT into the curriculum and encourage students to participate in CT ( Bower et al, 2017 ). They have attempted to teach and develop the knowledge and skills of CT in different educational situations by various means including programming ( Basu et al, 2017 ; Bati, 2021 ), educational robotics ( Chevalier et al, 2020 ; Qu and Fok, 2021 ), unplugged activities ( Kuo and Hsu, 2020 ; Huang and Looi, 2021 ), games/simulations ( Danial et al, 2021 ; Hooshyar et al, 2021 ), storytelling ( Soleimani et al, 2019 ; Parsazadeh et al, 2020 ), and so forth. These tools become “technical partners in the learning process” ( Jonassen et al, 2012 ), and the rationale for improving CT skills in each of these tools emphasizes various CT components ( Shute et al, 2017 ).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Computational thinking (CT) is considered to be a fundamental skill as important as reading, writing, and arithmetic, and is a set of thinking activities that draw on the basic concepts of computer science to solve problems, design systems, and understand human behavior [24]. While CT is associated with numerous hands‐on activities, such as robotics education, that can help develop CT skills [18], it is programming that is more closely related to CT. The close relationship between CT and programming stems from the fact that the essence of programming is writing programs to solve problems, and CT has the same connotation [1].…”
Section: Introductionmentioning
confidence: 99%